Silent Struggles of Foreign Fourth-Grade Primary School Students: Psychological Resilience and Invisible Traumas in Türkiye - Gürhan, Ethem (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study investigates the psychological resilience and invisible traumas of foreign fourth-grade primary school students in Türkiye, focusing on 91 students from Syrian, Iraqi, and Somali backgrounds in a public school in Konya. Using a qualitative research design, data were gathered through semi-structured interviews exploring students' migration histories, emotional struggles, school adaptation, and coping strategies. Findings reveal deep psychological distress linked to war, displacement, and migration-related adversities. Students frequently reported fear, social exclusion, and language difficulties, which hindered academic performance and integration. Despite these challenges, many displayed resilience through religious practices, creativity, and strong family ties. Peer interactions emerged as both supportive and discriminatory. While some teachers and peers contributed positively, trauma-informed approaches were largely absent. Guided by Bronfenbrenner's ecological systems theory and intersectionality, the study emphasizes the urgent need for comprehensive educational policies that include psychological support services, inclusive pedagogies, and robust language assistance. By highlighting these students' often-overlooked emotional experiences, the research contributes to the broader discourse on migration and education, offering practical recommendations for promoting equity and well-being in Turkish primary schools.